LAW ENFORCEMENT OF ILLEGAL BUSINESS TRANSACTION ON THE BORDER AREA BETWEEN INDONESIA AND TIMOR LESTE IN A DILEMMA - NLM Mahendrawati; I Gde Suranaya Pandit; IN Sujana; S Nahak; C.A. Soares; A. M. Telman (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2021)
This study is a type of empirical legal study conducted based on the discrepancy between the existing provisions and theories and the legal facts occurring among the society, that is, the transaction of goods carried out by crossing the border between two countries.Any hindering obstacles and barricades to the law enforcement over illegal businesses can be settled through social and cultural, economic, political, and security approaches. Alternative solutions that should be applied in dealing with such legal issues can be establishing buildings in the border area, which are specifically directed to help accelerate the handling of three fundamental problems faced in the scope of the development of the border area in question, one of which is delimitation and delineation aspects of the state's boundaries, the aspect of affirming national borders on watershed areas between Indonesia and Timor Leste, the aspect of development discrepancy in the form of fulfilling infrastructure needs in the economic field to foster opportunities for the border areas to participate and compete amid both global and regional markets.